Approaches to safe living and diet after solid organ transplantation. (28th July 2020) - Albert, Jonathan; Hanisch, Benjamin; Sgambat, Kristen
Abstract: SOT recipients are at high risk for developing severe infectious complications following discharge from the hospital. Comprehensive anticipatory guidance surrounding everyday lifestyle choices can potentially prevent exposure to infectious agents from the environment. This paper reviews the risks that pediatric and adolescent SOT recipients encounter through exposures such as household contacts, outdoor activities, travel, animal exposures, and dietary choices. Although strong evidence is lacking, this paper makes recommendations aimed at minimizing the risk of infectious complications and hospitalization in pediatric SOT recipients.